NUMERICAL STUDY OF SOIL SETTLEMENT BEHAVIOR ON PRELOADING EMBANKMENTS USING THE PLAXIS 2D FINITE ELEMENT METHOD - Johar Waluyo, Angga
Land subsidence is one of the most common problems encountered in earthworks. The nature of soft soil which has bad characteristics allows land subsidence over a long period of time. Finding efficient and effective soil improvement methods has been a constant challenge for construction companies and academia. The purpose of this study was to find out which soil modeling is the most optimal between Mohr-coulomb, soft soil and hardening soil to represent land subsidence that occurs in the application of soil improvement with the preloading method on the Indrapura - Kisaran Toll Road Project. The analysis was carried out using Plaxis 2D software which was developed based on the finite element method. Based on the results of monitoring the settlement plate in the field, it is known that the amount of settlement that occurs is 0.836 meters. The amount of land subsidence based on an analysis using the Mohr-Coulomb model is 0.779 meters or 6.65%. While using the hardening soil model is 0.802 meters or 4.43%, and the magnitude of the decrease using the soft soil model is 0.863 meters or 3.24%. Based on the pattern of settlement that occurs, the Mohr-Coulomb model is closer to the pattern of decline in field observations compared to soft soil and hardening soil. Thus it can be concluded that the calculation of consolidation settlement with Plaxis 2D using the Mohr-Coulomb model, soft soil or hardening soil gives satisfactory results where the difference in settlement analysis results with field monitoring is relatively small and the settlement pattern in the analysis results is close to the settlement pattern that occurs in the field.